A satellite‐based climatology of fog and low stratus formation and dissipation times in central Europe. (16th April 2022) - Pauli, Eva; Cermak, Jan; Andersen, Hendrik
Abstract: Knowledge of fog and low stratus (FLS) cloud patterns and life cycles is important for traffic safety, for the production of solar energy and for the analysis of cloud processes in the climate system. While meteorological stations provide information on FLS, a data set describing FLS formation and dissipation times on large spatial and temporal scales does not yet exist. In this study, we use logistic regression to extract FLS formation and dissipation times from a satellite‐based 10‐year FLS data set covering central Europe. The resulting data set is the first to provide a geographic perspective on FLS formation and dissipation at a continental scale. The patterns found show a clear dependency of FLS formation and dissipation times on topography. In mountainous areas, FLS forms in the night and dissipates in the morning. In river valleys, the typical FLS life cycle shifts to formation after sunrise and dissipation in the afternoon. Seasonal patterns of FLS formation and dissipation show similar FLS formation and dissipation times in winter and autumn, and in spring and summer, with longer events in the former two seasons. Abstract : A satellite‐based climatology of fog and low stratus (FLS) formation and dissipation times is created using logistic regression. The resulting data set is the first to provide a geographic perspective on FLS formation and dissipation at a large spatial scale. The patterns found show a clear dependence on topography of FLS formation and dissipation times, as shown here for dissipation.